HUBUNGAN STRES DENGAN KELANCARAN ASI PADA IBU MENYUSUI PASCA PERSALINAN Di RSI A.YANI SURABAYA - Rizki Amalia (Jurnal Ilmiah Kesehatan, 2016)
The relationship stress with the smoothness of breast milk in nursing mothers postpartum. Lactation has two understanding, they are formulating / the production of breast’s milk and resulting breast’s milk. Many factor influence the production of ASI, one of them is stress. The purpose of the research was to know the correlation between stress with the fluency of breast’s milk for breast feed’s mother of post labour in RSI A.Yani. The method which was used in the research was cross sectional analytic with non random sampling (quota sampling). The Population which was used in the research were all the second days’s post labour mother in RSI A.Yani And the member of samples used were 24 respondents. Collecting data by using questionnaire to know data of stress and the fluency of breast’s milk. The research result was gotten to the second days’s post labour mother in RSI A.Yani who experienced stress, experienced unfluency of giving breast’s Milk. After data was collected then it was tabulated and it was tested by using Spearman Rank Correlation. It was obtained the result that there was the correlation between stress with the fluency of breast’s milk for breast’s feed’s mother of post labour in RSI A.Yani. (Rho = 0,628). From the research it was hoped that the second days’s post labour mother could handle the emotion and psychology to think positively to be able to adapt well in their post partum periode so that the body has good response. Mothers did not experience stress and mother milk ran fluently.